Briquetting and pelleting the biomass: Protection from fire and explosions - Zvonko Nježić; Biljana Cvetković; Šandor Kormanjoš; Vojislav Banjac; Jasmina Živković (Zaštita Materijala)
Introduction of technologies that will produce up to 20% of energy from renewable sources is task that was set before our and all the other countries in the region, that aspire to EU accession. Biomass and production of briquettes and pellets are great advantages of our region. Production process has been processed throughout many studies, and this study focuses on safety and protection from adverse events that could occur during process. With proper implementation of all precautions from aspect of work safety and fire protection, proper performance of all technical details during work on the machines and during assembly of the equipment, along proper electric installations, proper handling and maintaining equipment and also with strict adherence to the prescribed work guidelines, it can be considered that fire hazards and explosive hazards are eliminated, or diminished to a minimum. That means that these hazards are not present in normal work conditions and that they can only arise due to certain irregularities during work. Prevention measures and their key aspects must be part of any serious study and technical technological documentation.